Investigation of the association between foot-and-mouth disease clinical signs and abattoir serological data in large ruminants in northern Lao People’s Democratic Republic - Gee, Emily; Young, James R.; Khounsy, Syseng; Phommachanh, Phouvong; Christensen, Peter; Theppangna, Watthana; Hughes, Tom; Brownlie, Tom; Temmerath, Adisone; Inthavong, Alex; Inthapanya, Phoummavanh; Punyasith, Sivone; et al. (Frontiers in Veterinary Science, 2024)
Foot-and-mouth disease (FMD) is a highly infectious endemic disease in Lao PDR. However, outbreaks are not routinely reported. To address this, serum samples were routinely collected from cattle and buffalo from provincial abattoirs between November 2021 and December 2022. In total, 2,663 serum samples were collected from1625 cattle and 1038 buffalo from 17 provinces. Samples were tested for specific antibodies directed against FMD non-structural protein (NSP) to determine the proportion of animals exposed to FMD virus. In addition to sampling from abattoirs, independent data was collected to report clinical signs and outcomes from 94 districts in 12 northern provinces. These incident reports were recorded by district staff using a Google Form and summarised monthly in the National Animal Disease Reporting System. Information was collected on species, incident date, herd size, location and which clinical signs the animals presented. Overall, 46% of the tested animals returned a positive result using ID Screen® FMD NSP Competition ELISA. Results from serological testing were then compared with reported clinical signs from the same district. In districts reporting ‘mouth problems’ (regardless of other clinical signs) the median FMD seroprevalence was 49.7%, compared to 31.6% in districts not reporting mouth problems (P = 0.021). This finding suggests that reporting clinical cases of ‘mouth problems’ could be a potential predictor of FMD at a district level in cattle and buffalo in Lao PDR. Furthermore, in districts reporting ‘fever’, ‘mouth problems’, and ‘nose/mouth secretions’ together, the median FMD seroprevalence was 46.2%, compared to 24.4% in districts not reporting these signs (P = 0.033). In districts reporting ‘mouth problems’ and ‘nose/mouth secretions’ the median FMD seroprevalence was 49.4%, compared to 25.5% in districts not reporting these signs (P = 0.037). In districts reporting both ‘fever’ and ‘mouth problems’, the median FMD seroprevalence was 46.4% compared to 25% in districts not reporting these signs (P = 0.017). Based on serological data generated by abattoir surveillance, this study identified clinical signs most predictive of FMD seroprevalence. These findings can help guide future passive surveillance in northern Laos and help support improved FMD surveillance more broadly in endemic countries in Southeast Asia.